The complete mitochondrial genome of the plant bug Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae: Bryocorinae: Dicyphini) - Dai, Xun; Xun, Huaizhu; Chang, Jian; Zhang, Jianguo; Hu, Baowen; Li, Hu; Yuan, Xiangqun; Cai, Wanzhi (Zootaxa, 2012)
Nesidiocoris tenuis (Reuter) is a zoophytophagous mirid which is considered both as a significant natural enemy and an important pest of crops. The complete mitochondrial genome (mitogenome) of N. tenuis was determined using long PCR and a primer walking sequencing strategy. The genome is 17, 544 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, two ribosomal RNA genes (lrRNA and srRNA), and a duplicate control region. The gene order of this newly sequenced genome is identical with the ground plan of insects. The nucleotide composition is biased toward adenine and thymine with a high AT content (75.0%). The most frequent codons are ATA, TTA, TTT, and ATT. All the PCGs initiate with the standard start codon ATN. All tRNAs have the classic cloverleaf structures, with the exception of tRNASer(UCG), which lacks the dihydrouridine (DHU) arm. Secondary structures of the two ribosomal RNAs were shown referring to previous models. Variable numbers of tandem repeats were detected in the control region. The phylogenetic analyses shows that N. tenuis is the sister group to Lygus lineolaris (Palisot de Beauvois).